1998
DOI: 10.1063/1.121268
|View full text |Cite
|
Sign up to set email alerts
|

Scanning capacitance microscopy imaging of threading dislocations in GaN films grown on (0001) sapphire by metalorganic chemical vapor deposition

Abstract: A combination of atomic force microscopy and scanning capacitance microscopy was used to investigate the relationship between the surface morphology and the near-surface electrical properties of GaN films grown on c-axis sapphire substrates by metalorganic chemical vapor deposition. Local regions surrounding the surface termination of threading dislocations displayed a reduced change in capacitance with applied voltage relative to regions that contained no dislocations. Capacitance–voltage characteristics obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
1
4

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(171 citation statements)
references
References 22 publications
10
156
1
4
Order By: Relevance
“…This leads us to suggest that dislocations are instead acting to impede current flow in localized regions, in effect causing a lateral inhomogeneity in which TD-localized regions restrict and divert current flow. This idea is supported by scanning capacitance microscopy studies 24 that showed evidence for significant negative charge buildup in the local vicinity of dislocations intersecting n-GaN surfaces causing higher localized Schottky barrier heights with respect to the surrounding material. This effect has also been observed by scanning Kelvin probe microscopy studies that reported an increase in surface potential of as much as 0.3-0.5 V across threading dislocations intersecting n-GaN surfaces, with a spatial full width at half maximum ͑FWHM͒ of 30-50 nm.…”
Section: B Reconciliation Of the Richardson Constant And Impact Of Tsupporting
confidence: 65%
See 1 more Smart Citation
“…This leads us to suggest that dislocations are instead acting to impede current flow in localized regions, in effect causing a lateral inhomogeneity in which TD-localized regions restrict and divert current flow. This idea is supported by scanning capacitance microscopy studies 24 that showed evidence for significant negative charge buildup in the local vicinity of dislocations intersecting n-GaN surfaces causing higher localized Schottky barrier heights with respect to the surrounding material. This effect has also been observed by scanning Kelvin probe microscopy studies that reported an increase in surface potential of as much as 0.3-0.5 V across threading dislocations intersecting n-GaN surfaces, with a spatial full width at half maximum ͑FWHM͒ of 30-50 nm.…”
Section: B Reconciliation Of the Richardson Constant And Impact Of Tsupporting
confidence: 65%
“…Moreover, earlier studies using scanning capacitance measurements performed on MOCVD grown n-GaN samples reported local raised barrier height regions of similar length scale to the radius determined in this study. 24 Finally, it is important to note, as shown in Fig. 5͑b͒, that this correction has no effect on the extracted SBHs and so remains consistent with the SBHs extracted from the I-V-T and IPE measurements.…”
Section: ͑8͒mentioning
confidence: 99%
“…Grains of similar size have also been observed by scanning capacitance microscopy. 13 The corresponding thresholded images are shown to accentuate the distribution of surface defects. The average measured hole diffusion lengths for both samples were the same to within experimental error; L p ϭ0.28Ϯ0.02 m. Figure 3 shows results for p-type MOCVD and n-type MBE grown GaN which also exhibited surface terminated defects.…”
Section: ͓S0003-6951͑98͒04649-x͔mentioning
confidence: 99%
“…which utilizes a tip-generated ac field to cause free carriers to be attracted and repelled by the tip for two-dimensional imaging ofcarrier dynamics in GaN films. Topography and SCM images are shown in Figure 5 [12) point out, however, it is~ible that the strain fields surrounding the defects and/or the piezoelectric fields associated with these strain fields could also lead to a voltage shift in the C -V curves.…”
Section: Investigation Of Defects By Spmmentioning
confidence: 99%
“…SPM-based techniques have been employed to perform high-resolution characterization of the local electronic properties of the III-nitrides . Local electronic properties of III-nitrides were first studied by Hansen et al [12] in 1998. They employed scanning capacitance microscopy (SCM) to investigate threading dislocations in GaN.…”
Section: Introductionmentioning
confidence: 99%